2010
DOI: 10.1007/s11270-010-0370-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In Situ Immobilization of Lead (Pb) and Arsenic (As) in Contaminated Soils with Phosphate and Iron: Solubility and Bioaccessibility

Abstract: The effect of in situ immobilization of lead (Pb) and arsenic (As) in soil with respectively phosphate and iron is well recognized. However, studies on combined Pb and As-contaminated soil are fewer, and assessment of the effectiveness of the immobilization on mobility and bioaccessibility is also necessary. In this study, a Pb and As-contaminated soil was collected from an abandoned lead/zinc mine in Shaoxing, Zhejiang province of China, which has been treated with three phosphates, i.e., calcium magnesium ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The pH value was significantly decreased in 1BC-1Fe(II) treatment owing that Fe(II) accounted for a significant portion of amendment. A similar result was reported by Cui [43], who found that addition of Fe(II) could obviously decrease the soil pH value. It is well known that the Fe-hydroxides may result in a lower pH.…”
Section: Discussionsupporting
confidence: 88%
“…The pH value was significantly decreased in 1BC-1Fe(II) treatment owing that Fe(II) accounted for a significant portion of amendment. A similar result was reported by Cui [43], who found that addition of Fe(II) could obviously decrease the soil pH value. It is well known that the Fe-hydroxides may result in a lower pH.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, lead (Pb) was chosen as the target heavy metal contaminant because it is one of the most toxic elements to human health, and a growing number of sites have been contaminated by Pb in China [9]. Within contaminated soils in the field, Pb speciation is controlled by: (1) specific adsorption or ion exchange adsorption to soil mineral matrix; (2) precipitation of sparingly soluble compounds; (3) formation of complexes with organic matter [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out on the behaviour of selenite in soils and pure phases (e.g. Chabroullet, 2007;Coppin et al, 2006;Darcheville et al, 2008;Dynes and Huang, 1997;Haudin et al, 2007;Øgaard et al, 2006;Sposito et al, 1988). However, only a few studies have been conducted on selenate, even though it is potentially the most mobile form (Séby et al, 1998), probably because it is not the major form of Se for in situ measurements (Wang and Gao, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This information could be of primary importance in chosing which mineral phases should be used to immobilise Se pollution in a contaminated area, as has already been done for other pollutants (e.g. Cui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%